TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Root Characteristics Vary with Depth Across Four Lowland Seasonal Tropical Forests - Amanda L. Cordeiro; Daniela F. Cusack; Lee H. Dietterich; William C. Hockaday; Karis J. McFarlane; Vinothan Sivapalan; Alexandra Hedgpeth; Avishesh Neupane; Lily Colburn; Weronika Konwent; Gabriel Oppler; Jacqueline C. Reu; et al. (Ecosystems, 2024)

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Divergent responses of soil microorganisms to throughfall exclusion across tropical forest soils driven by soil fertility and climate history - Stephany S. Chacon; Daniela F. Cusack; Aizah Khurram; Markus Bill; Lee H. Dietterich; Nicholas J. Bouskill (Soil Biology and Biochemistry, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Fine Root and Soil Organic Carbon Depth Distributions are Inversely Related Across Fertility and Rainfall Gradients in Lowland Tropical Forests - Daniela F. Cusack; Benjamin L. Turner (Ecosystems, 2021)

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

Reducing climate impacts of beef production: A synthesis of life cycle assessments across management systems and global regions - Daniela F. Cusack; Clare E. Kazanski; Alexandra Hedgpeth; Kenyon Chow; Amanda L. Cordeiro; Jason Karpman; Rebecca Ryals (Global Change Biology, 2021)
The global demand for beef is rapidly increasing (FAO, 2019), raising concern about climate change impacts (Clark et al., 2020; Leip et al., 2015; Springmann et al., 2018). Beef and dairy contribute over 70% of livestock greenhouse gas emissions (GHG), which collectively contribute ~6.3 Gt CO 2 ‐eq/year (Gerber et al., 2013; Herrero et al., 2016) and account for 14%–18% of human GHG emissions (Friedlingstein et al., 2019; Gerber et al., 2013). The utility of beef GHG mitigation strategies, such as land‐based carbon (C) sequestration and increased production efficiency, are actively debated (Garnett et al., 2017). We compiled 292 local comparisons of “improved” versus “conventional” beef production systems across global regions, assessing net GHG emission data from Life Cycle Assessment (LCA) studies. Our results indicate that net beef GHG emissions could be reduced substantially via changes in management. Overall, a 46 % reduction in net GHG emissions per unit of beef was achieved at sites using carbon (C) sequestration management strategies on grazed lands, and an 8% reduction in net GHGs was achieved at sites using growth efficiency strategies. However, net‐zero emissions were only achieved in 2% of studies. Among regions, studies from Brazil had the greatest improvement, with management strategies for C sequestration and efficiency reducing beef GHG emissions by 57%. In the United States, C sequestration strategies reduced beef GHG emissions by over 100% (net‐zero emissions) in a few grazing systems, whereas efficiency strategies were not successful at reducing GHGs, possibly because of high baseline efficiency in the region. This meta‐analysis offers insight into pathways to substantially reduce beef production's global GHG emissions. Nonetheless, even if these improved land‐based and efficiency management strategies could be fully applied globally, the trajectory of growth in beef demand will likely more than offset GHG emissions reductions and lead to further warming unless there is also reduced beef consumption.

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

Exotic grasses and nitrate enrichment alter soil carbon cycling along an urban–rural tropical forest gradient - Daniela F. Cusack; Joseph K. Lee; Taylor L. McCleery; Chase S. LeCroy (Global Change Biology, 2015)
Urban areas are expanding rapidly in tropical regions, with potential to alter ecosystem dynamics. In particular, exotic grasses and atmospheric nitrogen (N) deposition simultaneously affect tropical urbanized landscapes, with unknown effects on properties like soil carbon (C) storage. We hypothesized that (H1) soil nitrate ( NO 3 − ) is elevated nearer to the urban core, reflecting N deposition gradients. (H2) Exotic grasslands have elevated soil NO 3 − and decreased soil C relative to secondary forests, with higher N promoting decomposer activity. (H3) Exotic grasslands have greater seasonality in soil NO 3 − vs. secondary forests, due to higher sensitivity of grassland soil moisture to rainfall. We predicted that NO 3 − would be positively related to dissolved organic C ( DOC ) production via changes in decomposer activity. We measured six paired grassland/secondary forest sites along a tropical urban‐to‐rural gradient during the three dominant seasons (hurricane, dry, and early wet). We found that (1) soil NO 3 − was generally elevated nearer to the urban core, with particularly clear spatial trends for grasslands. (2) Exotic grasslands had lower soil C than secondary forests, which was related to elevated decomposer enzyme activities and soil respiration. Unexpectedly, soil NO 3 − was negatively related to enzyme activities, and was lower in grasslands than forests. (3) Grasslands had greater soil NO 3 − seasonality vs. forests, but this was not strongly linked to shifts in soil moisture or DOC . Our results suggest that exotic grasses in tropical regions are likely to drastically reduce soil C storage, but that N deposition may have an opposite effect via suppression of enzyme activities. However, soil NO 3 − accumulation here was higher in urban forests than grasslands, potentially related to of aboveground N interception. Net urban effects on C storage across tropical landscapes will likely vary depending on the mosaic of grass cover, rates of N deposition, and responses by local decomposer communities.

Consequence of altered nitrogen cycles in the coupled human and ecological system under changing climate: The need for long-term and site-based research - Hideaki Shibata; Cristina Branquinho; William H. McDowell; Myron J. Mitchell; Don T. Monteith; Jianwu Tang; Lauri Arvola; Cristina Cruz; Daniela F. Cusack; Lubos Halada; Jiří Kopáček; Cristina Máguas; et al. (Ambio, 2015)

The response of heterotrophic activity and carbon cycling to nitrogen additions and warming in two tropical soils - Daniela F. Cusack; Margaret S. Torn; William H. McDowell; Whendee L. Silver (Global Change Biology, 2012)

The response of heterotrophic activity and carbon cycling to nitrogen additions and warming in two tropical soils - DANIELA F. CUSACK; MARGARET S. TORN; WILLIAM H. McDOWELL; WHENDEE L. SILVER (Global Change Biology, 2010)
Nitrogen (N) deposition is projected to increase significantly in tropical regions in the coming decades, where changes in climate are also expected. Additional N and warming each have the potential to alter soil carbon (C) storage via changes in microbial activity and decomposition, but little is known about the combined effects of these global change factors in tropical ecosystems. In this study, we used controlled laboratory incubations of soils from a long‐term N fertilization experiment to explore the sensitivity of soil C to increased N in two N‐rich tropical forests. We found that fertilization corresponded to significant increases in bulk soil C concentrations, and decreases in C loss via heterotrophic respiration ( P 2 from fertilized cores had significantly higher Δ 14 C values than control soils, indicating losses of relatively older soil C. These results indicate that soil C storage is sensitive to both N deposition and warming in N‐rich tropical soils, with interacting effects of these two global change factors. N deposition has the potential to increase total soil C stocks in tropical forests, but the long‐term stability of this added C will likely depend on future changes in temperature.

Biological Nitrogen Fixation in Two Tropical Forests: Ecosystem-Level Patterns and Effects of Nitrogen Fertilization - Daniela F. Cusack; Whendee Silver; William H. McDowell (Ecosystems, 2009)

Controls on long‐term root and leaf litter decomposition in neotropical forests - DANIELA F. CUSACK; WENDY W. CHOU; WENDY H. YANG; MARK E. HARMON; WHENDEE L. SILVER (Global Change Biology, 2009)
Litter decomposition represents one of the largest annual fluxes of carbon (C) from terrestrial ecosystems, particularly for tropical forests, which are generally characterized by high net primary productivity and litter turnover. We used data from the Long‐Term Intersite Decomposition Experiment (LIDET) to (1) determine the relative importance of climate and litter quality as predictors of decomposition rates, (2) compare patterns in root and leaf litter decomposition, (3) identify controls on net nitrogen (N) release during decay, and (4) compare LIDET rates with native species studies across five bioclimatically diverse neotropical forests. Leaf and root litter decomposed fastest in the lower montane rain and moist forests and slowest in the seasonally dry forest. The single best predictor of leaf litter decomposition was the climate decomposition index (CDI), explaining 51% of the variability across all sites. The strongest models for predicting leaf decomposition combined climate and litter chemistry, and included CDI and lignin ( R 2 =0.69), or CDI, N and nonpolar extractives ( R 2 =0.69). While we found no significant differences in decomposition rates between leaf and root litter, drivers of decomposition differed for the two tissue types. Initial stages of decomposition, determined as the time to 50% mass remaining, were driven primarily by precipitation for leaf litter ( R 2 =0.93) and by temperature for root litter ( R 2 =0.86). The rate of N release from leaf litter was positively correlated with initial N concentrations; net N immobilization increased with decreasing initial N concentrations. This study demonstrates that decomposition is sensitive to climate within and across tropical forests. Our results suggest that climate change and increasing N deposition in tropical forests are likely to result in significant changes to decomposition rates in this biome.

Controls on long-term root and leaf litter decomposition in neotropical forests - DANIELA F. CUSACK; WENDY W. CHOU; WENDY H. YANG; MARK E. HARMON; WHENDEE L. SILVER (Global Change Biology, 2008)

Stoichiometry of soil enzyme activity at global scale - Robert L. Sinsabaugh; Christian L. Lauber; Michael N. Weintraub; Bony Ahmed; Steven D. Allison; Chelsea Crenshaw; Alexandra R. Contosta; Daniela Cusack; Serita Frey; Marcy E. Gallo; Tracy B. Gartner; Sarah E. Hobbie; et al. (Ecology Letters, 2008)
Extracellular enzymes are the proximate agents of organic matter decomposition and measures of these activities can be used as indicators of microbial nutrient demand. We conducted a global‐scale meta‐analysis of the seven‐most widely measured soil enzyme activities, using data from 40 ecosystems. The activities of β‐1,4‐glucosidase, cellobiohydrolase, β‐1,4‐ N ‐acetylglucosaminidase and phosphatase g −1 soil increased with organic matter concentration; leucine aminopeptidase, phenol oxidase and peroxidase activities showed no relationship. All activities were significantly related to soil pH. Specific activities, i.e. activity g −1 soil organic matter, also varied in relation to soil pH for all enzymes. Relationships with mean annual temperature (MAT) and precipitation (MAP) were generally weak. For hydrolases, ratios of specific C, N and P acquisition activities converged on 1 : 1 : 1 but across ecosystems, the ratio of C : P acquisition was inversely related to MAP and MAT while the ratio of C : N acquisition increased with MAP. Oxidative activities were more variable than hydrolytic activities and increased with soil pH. Our analyses indicate that the enzymatic potential for hydrolyzing the labile components of soil organic matter is tied to substrate availability, soil pH and the stoichiometry of microbial nutrient demand. The enzymatic potential for oxidizing the recalcitrant fractions of soil organic material, which is a proximate control on soil organic matter accumulation, is most strongly related to soil pH. These trends provide insight into the biogeochemical processes that create global patterns in ecological stoichiometry and organic matter storage.